Pengaruh Permainan Dende Bulang Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun di TK Negeri Songing - Andi Sri Putri Dewi; Muhammad Yusri Bachtiar; Sri Rika Amriani (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to determine the effect of the Dende Bulang game on the gross motor development of children aged 5-6 years at TK Negeri Songing. This research employed a quantitative approach with a quasi-experimental design involving two groups, namely the experimental group and the control group. The sample consisted of 16 children in group B selected using purposive sampling, comprising 8 children in the experimental group and 8 in the control group. Data were collected through treatment tests (pre-test and post-test), observations, and documentation. Data analysis utilized descriptive statistics to describe the gross motor development of children and non-parametric statistical analysis using the Wilcoxon test to examine differences before and after the intervention. The findings revealed a significant improvement in children's gross motor abilities after participating in the Dende Bulang game, particularly in aspects of balance, coordination, and agility. The Dende Bulang game was proven to have a positive influence as a learning intervention capable of stimulating gross motor development in early childhood. These results indicate that traditional games can be effectively integrated into PAUD learning activities as enjoyable and effective strategies to support children's gross motor skill development